Reconciling State and Society? The Practice of the Common Good in the Partnership of Bishop David Sheppard and Archbishop Derek Worlock. (24th December 2015) - Power, Maria
Abstract : The dynamic partnership between Anglican Bishop, David Sheppard, and his Roman Catholic counterpart, Derek Worlock, was a significant force in Liverpool during the 1980s, both ecumenically and politically. However, despite their "cult status" within the city, their national and international importance has yet to be explored. The 1981 Toxteth Riots are used as a case study through which to read their exceptional and transformative relationship. This article will discuss how their partnership became emblematic of changing church–state relationships from both Anglican and Roman Catholic perspectives, and how they each, in turn, went on to shape their churches' dialogue with the government. The article explores the nature of their collaboration and the theological and doctrinal ideas that informed it, before going on to discuss the 1981 Riots in detail. It will demonstrate that the Sheppard–Worlock model of ecumenism put the Gospel, and in particular its focus upon the poor and marginalised, at the heart of their partnership. It will conclude that they sought the Common Good for society and believed that reconciliation was the key to the achievement of this goal.